Notes on the Neurigona Rondani (Diptera: Dolichopodidae) from Chinese Mainland - Wang, Mengqing; Yang, Ding; Grootaert, Patrick (Zootaxa, 2007)
The following seven new species of the genus Neurigona are described and illustrated: Neurigona guangdongensis Wang, Yang and Grootaert sp. nov., N. guizhouensis Wang, Yang and Grootaert, sp. nov., N. henana Wang, Yang and Grootaert, sp. nov., N. jiangsuensis Wang, Yang and Grootaert, sp. nov., N. wui Wang, Yang and Grootaert, sp. nov., N. xiaolongmensis Wang, Yang and Grootaert, sp. nov. and N. yunnana Wang, Yang and Grootaert, sp. nov. We examined the male holotype of N. grisea Parent and female holotype of N. chetitarsa deposited in Muséum National d’Historie Naturelle, Paris. Also, the new data on distribution are reported for four known species. A key to the species of the genus from Chinese mainland is presented.